The Application of Marketing Psychology to Enhance MSME Competitiveness: Indonesia–Malaysia Collaboration - Dyah Rachman Kuswartanti; Agung Pramayuda; Aggi Panigoro; Vika Aprianti; Hamzah Zuyyina Rahmat; Rahma Nafilatun Nisa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the economy in Indonesia and Malaysia, yet they face challenges in marketing strategies, particularly in understanding consumer psychology. This community service activity, titled “Application of Marketing Psychology to Enhance MSME Competitiveness: Indonesia–Malaysia Collaboration,” aims to improve MSME capacity through understanding consumer behavior, motivation, perception, and attitudes in marketing. The program was conducted in a hybrid format at el Royal Hotel Bandung and via Zoom Meeting, involving MSMEs from both countries as well as students and academics. The methods employed included lectures and interactive Q&A sessions to provide practical understanding. The results indicated increased participant awareness of the importance of brand storytelling, emotional engagement, and effective communication strategies. Participants began to utilize social media more strategically and build emotional connections with consumers. Cross-country collaboration enriched the exchange of experiences, combining creativity and digitalization while strengthening regional competitiveness. In conclusion, applying marketing psychology proved effective in enhancing MSME capacity and confidence to develop sustainable businesses, build strong brand identity, and foster long-term customer relationships.